Nurse’s Experience of Psychological Changes in Caring for Covid-19 Patients During Pandemic - Wahyi Sholehah Erdah Suswati; Asti Melani Astari; Retno Lestari (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The pandemic of COVID-19 had a psychological impact on health workers especially for nurses. They experienced anxiety, insomnia, depression and phobias during treating COVID-19 patients. The study aimed to explore the psychological experience of nurses in caring for COVID-19 patients during pandemic. The interpretive phenomenological approach was applied to collected data via zoom meeting cloud. 10 nurses were recruited purposively based on the spesific criteria. The findings were analyzed using the interpretive phenomenological analysis (IPA) technique and revealed 9 categories include: 1) accept the task half-heartedly, 2) fear of the impact of a given task, 3) depressed when first encountering the situation, 4) always have to be careful and disciplined with work safety protocols, 5) faith and confidence in God will give strength, 6) able to control feelings and seek help, 7) get moral and material support, 8) caring grows when dealing with patients being treated, and 9) sincerely enjoying work as part of a nurse's duties. The survival and growth in the stressful situations is the major theme of the study. The organizational institution should give support to the frontline nurses by providing psychological screening examination, regular monitoring, intervention training to improve nurses ability in psychological care independently.Abstrak: Pandemi COVID-19 mengakibatkan dampak psikologis bagi tenaga kesehatan khususnya perawat. Perawat mengalami kecemasan, insomnia, depresi, dan phobia selama merawat pasien COVID-19. Penelitian ini bertujuan mengeksplorasi pengalaman psikologis perawat selama merawat pasien COVID-19. Penelitian menggunakan pendekatan fenomenologi interpretif melalui wawancara mendalam kepada 10 partisipan yang dipilih secara purposive sesuai kriteria tertentu. Pengambilan data melalui zoom meeting cloud. Analisis data menggunakan teknik interpretive phenomenological analysis (IPA) menghasilkan 9 tema antara lain: 1) menerima tugas dengan setengah hati; 2) ketakutan terhadap dampak dari tugas yang dijalankan; 3) tertekan ketika pertama kali menghadapi situasinya; 4) mengharuskan diri selalu berhati-hati dan disiplin protokol keselamatan kerja; 5) kepercayaan dan keyakinan kepada Tuhan memberi kekuatan; 6) berupaya mengendalikan perasaan dan mencari bantuan; dan 7) mendapatkan dukungan moril maupun materiil; 8) kepedulian tumbuh saat menghadapi pasien yang dirawat; dan 9) ikhlas menikmati pekerjaan sebagai bagian dari tugas seorang perawat. Terdapat pertumbuhan aspek psikologis dari negatif menjadi positif pada diri perawat seiring berjalannya waktu. Perawat bertahan dan bertumbuh dalam situasi penuh tekanan menjadi tema besar penelitian ini. Rumah sakit perlu mendukung perawat dengan cara melakukan pemeriksaan dan pemantauan psikologis rutin, menyediakan pelatihan untuk meningkatkan kemampuan perawat dalam perawatan psikologis secara mandiri, serta menyediakan dukungan psikologis profesional jika diperlukan.